Factors determining blended learning receptiveness among Malaysian academicians - Nurjeehan Ayub; Md Hafizi Ahsan @ Miskam; Nur Shahirah Azman (Penerbit UMS, 2021)
This study aimed to reveal the level of blended learning receptiveness among Malaysian academicians strictly during the Covid-19 pandemic, and applied the Theory of Planned Behaviour (TPB) in examining the factors determining blended learning receptiveness among Malaysian academicians. Malaysian higher learning institutions practised blended learning following learning method efficiencies and the significance of the Malaysia Education Blueprint 2025. Five independent variables (attitudes, subjective norms, and perceived behavioural control, organisational assistance, and literacy) were investigated in the study context. Specifically, 250 questionnaires were distributed to respondents during the working hours of chosen private universities. Smart Partial least squares (PLS) analysis tool is employed to examine the model fits and hypothesis testing. Findings show that all variables have a positive and significant relationship with the receptiveness of blended learning among academicians. Thus, this study shows that blended learning receptiveness is high, especially during pandemic and lockdown situations. This study proved essential for Malaysian academicians, specifically regarding blended learning utilization and implementation. As blended learning was predictably time-consuming and deterred the implementation process, this study strived to promote blended learning among Malaysian educators. The Covid-19 pandemic resulted in the complete utilization of blended learning using digital platforms. Most academicians could not conduct face-to-face classes due to the restrictions on physical contact. Hence, this study proved essential for educators in wholly implementing blended learning amid the outbreak.